2016
DOI: 10.1103/physrevlett.116.226401
|View full text |Cite
|
Sign up to set email alerts
|

Insulating Nature of Strongly Correlated Massless Dirac Fermions in an Organic Crystal

Abstract: Through resistivity measurements of an organic crystal hosting massless Dirac fermions with a charge-ordering instability, we reveal the effect of interactions among Dirac fermions on the charge transport. A low-temperature resistivity upturn appears robustly irrespectively of pressure and is enhanced while approaching the critical pressure of charge ordering, indicating that the insulating behavior originates from short-range Coulomb interactions. Observation of apparently vanishing gap in the charge-ordered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 43 publications
16
85
0
Order By: Relevance
“…7(b). However, in contrast to (TMTTF)2X where the spins are intact at the transition, the CO transition in -I3 is accompanied by a concomitant spinsinglet formation as a consequence of the strong dimerization [1,3,17,18,20,30,31].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…7(b). However, in contrast to (TMTTF)2X where the spins are intact at the transition, the CO transition in -I3 is accompanied by a concomitant spinsinglet formation as a consequence of the strong dimerization [1,3,17,18,20,30,31].…”
Section: Discussionmentioning
confidence: 80%
“…However, the presence of the low-energy linear spectrum near EF is hidden at low T beneath the first-order chargeordering (CO) transition taking place at TCO ≈ 135K [1,3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] due to strong electron correlations [28,29]. The transition is accompanied by an opening of an energy gap in the charge and spin excitation spectra and a formation of quasi-one-dimensional (quasi-1D) charge stripes along the crystalline b axis [14], leading to an insulating spin-singlet ground state [1,3,17,18,20,30,31]. The inversion centers, locating on the molecules B and C and in between the molecules A and A' at T > TCO [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We do not see indication of a complete energy gap or pseudogap in our data, as inferred from the low-temperature upturn in the high-pressure resistivity 13 ; future experiments at lower temperatures and smaller frequencies might clarify this controversy. It is interesting to note the recent results on a low-energy gap in the Dirac system α-(BEDT-TTF) 2 I 3 where strong correlations eventually become effective 25,26 .…”
Section: Results and Analysismentioning
confidence: 99%
“…Tajima et al have observed from the conductivity that the charge ordering disappears at an uniaxial pressure, P 10 kbar 43 . In the hydrostatic pressure, the charge ordering has not been observed above 17 kbar from the magneto conductivity 44 and above 11−12 kbar from the optical investigations 45 and conductivity 46 . In this paper we do not study the interaction between electrons, so we do not concern the metal-insulator transition caused by the charge ordering.…”
Section: Introductionmentioning
confidence: 91%